Ethical issues in aviation - Hoppe, Elizabeth (Elizabeth Anne) (Farnham, Surrey, England : Burlington, VT ; Ashgate, 2011)
This book focuses on current concerns and trends, to reflect the changes that have occurred in this deregulated era. It provides the reader with an overview of the major themes in civil aviation ethics. The book begins with theoretical frameworks, followed by sections on the business side of aviation, employee responsibility, diversity in aviation, ground issues regarding airports, air traffic control and security, as well as health and the environment.
a pt. I. Theoretical frameworks. Ethical theories part I : dilemmas and decision-making ; Ethical theories part II : rights and character ; Capitalism and its critics -- pt. II. The business of aviation. Who governs international aviation? ; Making prices right : challenges facing airline managers and consumers ; Outsourcing under systems integration : the long run benefits for Boeing and other aircraft ; Outsourcing maintenance : a union perspective -- pt. III. Issues in responsibility. Whistleblowing in aviation ; Ethics and FAA inspectors ; The danger of capture in the FAA ; Learning to compete wisely : a primer in creating pilot unity ; Ethics in aviation from the perspective of a flight attendant ; ValuJet 592 and corporate responsibility -- pt. IV. diversity in aviation. Racial discrimination against pilots : an historical perspective ; Gender and racial barriers in flight training ; Diversity recruiting in aviation maintenance ; Safety, economic favoritism, or age discrimination? The story behind the FAA's age 60 rule -- pt. V. Airports, ATC, and security. There goes the neighborhood : conflicts associated with the location and operation of airports ; Chicago O'Hare and the politics of airport expansion ; The ethical dimensions of the 1981 PATCO strike ; Air traffic control : a critical system in transition ; The TSA and risk management : are we safer today? -- pt. VI. Health and the environment. Ethical issues in aviation medicine ; Environmental concerns in general aviation : Avgas and noise pollution ; Greenhouse gas emissions, persistent contrails, and commercial aviation ; Ground-level pollution, invasive species, and emergent diseases.
Includes bibliographical references and index.
Keywords: Aeronautics, Commercial -- Moral and ethical aspects; Aeronautics -- Social aspects